Examination of the Al6013 Alloy Coated with Graphene/Fly Ash-Expanded Perlite by Hydrothermal Method - Muratoglu, Mehtap; Baydemir, Selin (Springer Heidelberg, 2023)
This study was aimed to apply coatings on an aluminum alloy with solutions prepared in graphene/fly ash-expanded perlite combinations with the hydrothermal method. Hybrid Composite Coating solutions were prepared by using 0.1 wt.% graphene _10-30 wt. % fly ash and 0.1 wt.% graphene _10-30 wt. % expanded perlite. Al6013 alloy substrates were subjected to the coating process for 24 h at 240 degrees C using these solutions in a hydrothermal device. The coated specimens were subjected to a sintering heat process for 1 h at 450 degrees C. Scanning electron microscopy, energy dispersive X-ray analysis (EDX), X-ray diffraction analysis (XRD), surface roughness and microhardness tests were conducted for hybrid composite coated specimens. It generally was observed that in the form of randomly divided, uniform and thin layers in a stratified manner and with a graphene-like structures. As the reinforcement ratio of fly ash and expanded perlite increased, the microhardness values showed an increase. The highest hardness among all specimens was observed in the 0.1 wt. % graphene-30 wt. % expanded perlite reinforced specimen. In the fly-ash reinforced specimens, as the reinforcement ratio increased, the coating thickness increased up to the specimen with 20wt. % fly ash addition, and then, decreased. Also, it was observed that the coating thickness increased as the expanded perlite reinforcement ratio increased.
Keywords: Hydrothermal method; Graphene; Expanded perlite; Fly ash; Al6013 alloy